SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN KELAYAKAN MAHASISWA DALAM MENGIKUTI PROGRAM KAMPUS MENGAJAR MENGGUNAKAN METODE MOORA: (Studi Kasus : STMIK Kaputama) - Wati, Sri Kesuma; Fauzi, Achmad; Saragih, Rusmin (Journal of Engineering, Technology and Computing (JETCom), 2023)
Merdeka learning Merdeka Learning Merdeka Campus (MBKM) is a program designed by the Minister of Education and Culture which aims to encourage students to master various sciences to prepare them to enter the world of work. The Merdeka Learning Campus Merdeka Program (MBKM) is one of the breakthroughs of the Ministry of Education, Culture, Research and Technology in spurring quality and character human resources, because through this planned program, it is hoped that both students and lecturers will have different experiences which in the end will enrich insight, network, and character excellence. In order to prepare students to face social, cultural, world of work changes and rapid technological advances, student competencies must be prepared to be more relevant to the needs of the times.